Religious Associational Life amongst Black African Christian Students at Howard College Campus, University of KwaZulu-Natal - Anthonia Ishabiyi; Sultan Khan (Journal for the Study of Religion)
Historically, religion has played a key role in the destiny of human beings. It has provided reasons for its existence and shaped the social, cultural, economic, and political behavior of individuals and society. Specifically in the 21st century, the globe has become a multi-faith space with diverse religious philosophies, ways of religious expressions, norms, and values. For the young university students, it provides a space for critical reflection, awareness of one’s self and an environment in which one’s values and norms are tested and perhaps reshaped. Given the abstractness of the university environment and exposure to a vast range of beliefs and practices, it may challenge the religious belief structure of students to an extent that one may go on to question long held religious beliefs and practices. It is against the background of this context that this article tests the nature of religious associational life of on-campus black African Christian students at the University of KwaZulu-Natal, Howard College Campus. The methodological approach to the study embraced both qualitative and quantitative data gathering tools. Semi-structured self-administered questionnaires were used to gather data. A total of 123 respondents, selected purposively, participated in the study. The results of this study suggest that on-campus, religious associations play an integral role in reinforcing the religious and spiritual identity of students. It impacts both their personal and academic life. Additionally, the study highlights that although religious tolerance featured in the study, there was a need for inter-religious dialogue, given the diversity of faith groups in the country.